Education, Work and Development - Pastore, José (2013)
The article seeks to show the importance of education as a driver of a country’s economic growth. Production processes are increasingly rooted in “intangible assets” (i.e. ideas). For a country to be successful, it is not simply a question of its citizens being “informed”. Nations need to know how to use information and turn it into a productive asset. Technological changes are occurring at unprecedented speed. The same machines are used in most countries and are becoming increasingly affordable worldwide. What will mark the winners from the losers in the future is the ability to use this equipment efficiently. Good professional training is called for. It is indeed a strategic requirement. It is through quality education that people acquire the ability to reason, think and act. Brazil is seriously lagging behind in terms of basic and higher education. Improving the quality of teaching is absolutely crucial. The role of education in driving progress has never been clearer.